Effects of cooking on the flavonoid content and radical scavenging activity of bitter gourd (Momordica charantia) crude extracts - Balin, Kimberly D. (College of Home Economics, University of the Philippines Diliman, 2013)
This study aimed to determine the effects of cooking on the flavonoid content and radical scavenging activity of the leaves and fruits of the two types of Momordica charantia - hybrid and wild - normally consumed in Filipino households. Samples cooked for 5 and 10 minutes using water and oil-water as heating media in a cooking pan with and without lid were analyzed for the amount of flavonoids (mg CE/100 g sample) and antioxidant activity (IC50) The media used for cooking were analyzed similarly. The plant types and plant varieties to be studied were based on interviews with people who consume and/or cook Momordica charantia. The cooking conditions used were also based on the usual ways this vegetable is consume as revealed by the respondents in the interviews. Methanol was chosen as the extraction solvent since preliminary study showed that methanol is the best solvent for flavonoid extraction, giving the highest amount of extracted flavonoids, as compared to other solvents of lower polarity. Results showed that generally, the wild type has higher content of flavonoids than the hybrid type, and the leaves more than the fruits. Cooking method significantly (p < 0.05) decreases the flavonoid content but at the same time significantly (p < 0.05) increases the radical scavenging activity of Momordica charantia hybrid and wild type fruits and leaves. The cooking time is proportional to the degree of loss and degree of gain in flavonoid and radical scavenging activity, respectively. The oil added on the heating medium did not affect the results. Samples cooked with pan lid have less flavonoids than those cooked without. Analysis of the heating medium showed leaching of the flavonoids with radical scavenging activity from the vegetable to the cooking medium.